Sleep quality, APOE ε4, and Alzheimer’s disease: associations from two prospective cohort studies and mechanisms by plasma proteomic analysis - Liang-Yu Huang; Lan Tan; Chen-Chen Tan; Xin-Yu Zhang; Xu Lin; Juan-Juan Zou; Yu-Jing Lin; Yu-Ying Zhang; Quan Hao; Zi-Qi Zhang; for the Alzheimer’s Disease Neuroimaging Initiative; Wei Xu (BMC Medicine)
Abstract Background The relationship between sleep quality and Alzheimer's disease (AD), and its interaction with genetic susceptibility, remains unclear. Our study explores the complex association between sleep quality and AD risk, focusing on the moderating role of the APOE ε4 allele. Methods Linear regression models, linear mixed-effects models, and Cox proportional hazard models were conducted in 321,905 non-demented participants from UK Biobank (UKB, mean age = 56.49, mean follow-up: 12.3 years) and 1,598 non-demented participants (mean age = 73.19, mean follow-up: 3.90 years) from Alzheimer's Disease Neuroimaging Initiative (ADNI). The interaction terms of sleep by APOE ε4 status were added in all analyses and stratified analyses were further performed. Proteomic and bioinformatic analyses were conducted to explore the biological mechanisms by which sleep and its interaction with APOE ε4 influence the development of AD. Results Poor sleep quality was significantly associated with worse cognition, faster hippocampal atrophy, and increased AD risk (HR = 1.05 in UKB and HR = 1.37 in ADNI). Notably, these associations were intensified in APOE ε4 carriers. Proteomic analyses identified eleven proteins linked to both poor sleep and AD risk (P < 1.72 × 10–5). These proteins were enriched mainly in inflammatory and metabolic pathways. Growth differentiation factor 15 was identified as the bridge linking poor sleep and AD risk specifically in APOE ε4 carriers. Conclusions Poor sleep is associated with increased risk of AD, possibly by dysregulating peripheral inflammatory responses and metabolic pathways. The interaction between poor sleep and APOE ε4 may further enhance AD risk. Future studies are warranted to test whether this interaction was driven by neuroinflammation.